Bile acid signalling and its role in anxiety disorders - Chen, Simin; Shao, Qi; Chen, Jiayi; Lv, Xinyi; Ji, Jing; Liu, Yan; Song, Yuehan (Frontiers in Endocrinology, 2023)
Anxiety disorder is a prevalent neuropsychiatric disorder that afflicts 7.3%~28.0% of the world's population. Bile acids are synthesized by hepatocytes and modulate metabolism via farnesoid X receptor (FXR), G protein-coupled receptor (TGR5), etc. These effects are not limited to the gastrointestinal tract but also extend to tissues and organs such as the brain, where they regulate emotional centers and nerves. A rise in serum bile acid levels can promote the interaction between central FXR and TGR5 across the blood-brain barrier or activate intestinal FXR and TGR5 to release fibroblast growth factor 19 (FGF19) and glucagon-like peptide-1 (GLP-1), respectively, which in turn, transmit signals to the brain via these indirect pathways. This review aimed to summarize advancements in the metabolism of bile acids and the physiological functions of their receptors in various tissues, with a specific focus on their regulatory roles in brain function. The contribution of bile acids to anxiety via sending signals to the brain via direct or indirect pathways was also discussed. Different bile acid ligands trigger distinct bile acid signaling cascades, producing diverse downstream effects, and these pathways may be involved in anxiety regulation. Future investigations from the perspective of bile acids are anticipated to lead to novel mechanistic insights and potential therapeutic targets for anxiety disorders.